2021
DOI: 10.1128/mbio.00673-21
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Binds to Host Lactate Dehydrogenase via PspA and PspC To Enhance Virulence

Abstract: Pneumococcal surface protein A (PspA) and pneumococcal surface protein C (PspC, also called CbpA) are major virulence factors of Streptococcus pneumoniae (Spn). These surface-exposed choline-binding proteins (CBPs) function independently to inhibit opsonization, neutralize antimicrobial factors, or serve as adhesins. PspA and PspC both carry a proline-rich domain (PRD) whose role, other than serving as a flexible connector between the N-terminal and C-terminal domains, was up to this point unknown. Herein, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 58 publications
1
28
0
Order By: Relevance
“…The ability of PspA to mediate bacterial attachment to dying cells is perhaps the most straightforward explanation for how it contributes to enhanced pneumonia severity. We speculate that in addition to helping the bacteria avoid mucociliary clearance, the close physical interaction of Spn with dying lung cells also serves to enhance the bacterium’s accessibility to any released nutrients or host proteins that could be co-opted by Spn ( Park et al, 2021 ; Sender et al, 2020 ). These would otherwise be diluted within the mucosal secretions.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of PspA to mediate bacterial attachment to dying cells is perhaps the most straightforward explanation for how it contributes to enhanced pneumonia severity. We speculate that in addition to helping the bacteria avoid mucociliary clearance, the close physical interaction of Spn with dying lung cells also serves to enhance the bacterium’s accessibility to any released nutrients or host proteins that could be co-opted by Spn ( Park et al, 2021 ; Sender et al, 2020 ). These would otherwise be diluted within the mucosal secretions.…”
Section: Discussionmentioning
confidence: 99%
“…In our studies that identified PspA as having affinity to lactate dehydrogenase and GAPDH, it was observed that PspA also had affinity to numerous other host proteins (Park et al, 2021a;Park et al, 2021b). Among these was the filamentous protein vimentin, which has been implicated as a key ligand for group B Streptococci and E. coli with regard to their ability to gain access to the central nervous system (Deng et al, 2019).…”
Section: Other Interactionsmentioning
confidence: 92%
“…Curates PC residues on pneumococcal surface (Gosink et al, 2000;Hermoso et al, 2005) Choline McDaniel et al, 1986;McDaniel et al, 1987;Shaper et al, 2004;Mukerji et al, 2012;Park et al, 2021a;Park et al, 2021b) Pneumococcal choline-binding protein A…”
Section: Name Abbreviation Functionmentioning
confidence: 99%
See 2 more Smart Citations